2015
DOI: 10.4034/pboci.2015.151.27
|View full text |Cite
|
Sign up to set email alerts
|

Access to Dental Services and Related Factors in Adolescents from Vitória, Espírito Santo, Brazil, 2011

Abstract: Objective: To characterize access of adolescents to dental services and identify its determinants. Material and Methods: This is a cross-sectional, population-based study conducted with a representative sample of 431 adolescents aged 15-19 years in a health district of Vitória, ES. The interviews were guided by a structured questionnaire with socio-demographic questions, service utilization, and self-perceived oral health. SPSS statistical software version 15.0 was used. Statistical analysis consisted of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
2
3
0
8
Order By: Relevance
“…Routine visit to the dentist was reported by half of adolescents, corroborating the findings of previous study conducted in Southeastern Brazil [30,31] Patients with eating disorders are more likely to hide and deny their condition, thus avoiding the help of health professionals [26]. After evaluating women aged 18 years or older with diagnosis of bulimia nervosa, US researchers found that the majority (70.8%) reported that they had not talked with oral health professionals about their problem, and the causes related to this barrier between patient and oral health professional were mainly embarrassment (81.1%), shame (77.6%) and fear (54.2%) [22].…”
Section: Discussionsupporting
confidence: 80%
“…Routine visit to the dentist was reported by half of adolescents, corroborating the findings of previous study conducted in Southeastern Brazil [30,31] Patients with eating disorders are more likely to hide and deny their condition, thus avoiding the help of health professionals [26]. After evaluating women aged 18 years or older with diagnosis of bulimia nervosa, US researchers found that the majority (70.8%) reported that they had not talked with oral health professionals about their problem, and the causes related to this barrier between patient and oral health professional were mainly embarrassment (81.1%), shame (77.6%) and fear (54.2%) [22].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, in a study with adolescents aged 15-19 years, it was observed that most of those who have never been to the dentist were male [20]. However, although sex may affect the oral care level of individuals [21], periodontal conditions evaluated in this study were similar, regardless of sex.…”
Section: Discussionmentioning
confidence: 50%
“…Some researchers have shown that women have better health-related attitudes and behaviors, with a higher frequency in dental care services [20] and better oral hygiene performance [18]. In addition, in a study with adolescents aged 15-19 years, it was observed that most of those who have never been to the dentist were male [20].…”
Section: Discussionmentioning
confidence: 99%
“…A predominance of females (66.1%) among victims was observed, corroborating previous findings. [ 3 ] However, there may have been underreporting of accidents by male students since as women are more cautious about their health and tend to have greater preventive self-care,[ 12 17 ] they are possibly more attentive to the need to follow postexposure protocols and therefore cause a greater demand for the service.…”
Section: Discussionmentioning
confidence: 99%